Adsorption of heavy metals using magnetically modified alginic acid - Jeon, Choong; Nah, In Wook; Hwang, Kyung-Yub (ELSEVIER SCIENCE BV, 2007)
To improve efficiency of adsorption process, magnetically modified alginic acid (MMA) was synthesized by means of entrapment method with iron oxide and urethane. MMA had a high uptake capacity of 1.45 mmol/g-dry mass for lead ion at pH 4 and its uptake capacity was higher than that of the commercial ion exachanger (IR-120(+)) and activated carbon. The surface condition and existence of lead ions on the bead was confirmed by the FT-IR, SEM, and EDX instrumental analyses. When 0.6 g of MMA was added to initial heavy metal solution (Pb2+; 300 mg/L, Cd2+; 3 mg/L) removal efficiency of lead and cadmium ions was 100 and 80%, respectively. To increase removal efficiency of heavy metals, step-by-step addition of MMA was applied to heavy metal solution and it increased removal efficiency of heavy metals about 10%. In terms of kinetics, adsorption of heavy metals was almost completed in 10 min. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: REMOVAL; COPPER; GEL